PENGENALAN ALAT TRANSPORTASI KERETA API PADA ANAK USIA DINI - Damayanti, Ajeng Tyas; Astuti, Septiana Widi; Atmaja, Dadang Sanjaya; Dewi, Puspita; Puspitasari, Mariana Diah (Politeknik Perkeretaapian Indonesia Madiun, 2024)
Early childhood education is the main education towards higher education. Early childhood education must pay attention to the maturity of children in all aspects of life. Knowledge and understanding of something can be instilled into early childhood by various methods. In instilling understanding in children through direct recognition so that children will be stimulated through hearing (auditory) and sight (visual). The introduction of means of transportation is usually an attraction in itself for early childhood. Transportation tools become easy to understand because they are often seen even using these means of transportation. The introduction of means of transportation is carried out through auditory, visual and psychomotor. Improved auditory and visual abilities are obtained by the method of telling stories about trains. Videos are also shown to facilitate the child's understanding. Increasing children's knowledge and psychomotor using field trips directly by train to gain experience